Research at Teacher Training Colleges in Switzerland: present situation and scopes - Weiss, Jacques (Swiss Journal of Educational Research, 2018)
Research at Teacher Training Colleges (in Switzerland called Hautes Ecoles Pédagogiques – HEP) -institutions for studies in education – needs to be part of the curriculum of the introductory and continuing education for teachers at kindergarten, primary and secondary school levels. What the nature of the research will be, what topics it will deal with, who will conduct it, and how it will be conducted, are questions that will need to be answered. In order to determine what type of research should be carried out at the Teacher Training Colleges, the article examines the type of research conducted at different universities. Answers to the preceding questions can be found in institutions abroad that have acquired some experience in this domain, such as in France at the University Institutes of Education (Instituts universitaires de formation des maîtres), as well as in Quebec, where studies in education have already been carried out at universities for a significant number of years.So what is the status in Switzerland at the moment of the opening of these new training and research institutions? It is no surprise that in a federalist state such as Switzerland, the conceptions and their application vary from one canton to another. Thus, several different projects are being proposed, from which, nonetheless, certain common ideas result, namely, the importance of dedicated research regarding training for teachers and the necessity for trainers and researchers with scientific competence.